From individual care trajectories to HIV care cascade at population level in rural KwaZulu-Natal (South Africa): the impact of population dynamics - (:unkn) unknown (My University, 2018)
IntroductionThe universal test-and-treat strategy (UTT) was developed to maximize the proportion of all HIV-positive individuals on antiretroviral and virally suppressed, assuming that it leads to reduction in HIV incidence. The evolution over time of the cross-sectional population HIV care cascade is determined by longitudinal individual trajectories through the HIV care continuum and the underlying HIV population dynamics. This structural effect could dilute the impact observed at population level of a UTT strategy RT: either add impact on what (incidence) or delete sentence. The purpose of this paper is to quantify the contribution of each component of population change on the population HIV care cascade in the context of UTT.SampleWe used prospective individual-level longitudinal data from the ANRS 12249 cluster-randomized trial which was implemented in rural KwaZulu-Natal, South Africa between 2012 and 2016 to test such an approach.MethodsHIV tests results and information on clinic visits, ART prescription, viral load and CD4 count, migration and deaths were used to calculate residency status, HIV status and HIV care status for each individual on a daily basis. Position within the HIV care continuum was considered as a score ranging from 0 (undiagnosed) to 4 (virally suppressed). We compared the cascade score of each individual joining or leaving the HIV population with the average score of their cluster at the time of entry or exit. Then, we computed the contribution of each event on the average cascade score and the annualised total contribution of all events, considering 5 components of HIV population change: aging into the cohort, HIV seroconversions, in-migrations, out-migrations, and permanent exits (including deaths).ResultsWhile the average cascade score increased over time in all clusters, that increase was limited due to population dynamics, the total contribution of all population entries and exits being negative. Permanent exits and in
Keywords: African Research